2001
DOI: 10.1002/jnr.1186
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the 5‐lipoxygenase pathway in the neurotoxicity of the prion peptide PrP106‐126

Abstract: Transmissible spongiform encephalopathies are characterised by the transformation of the normal cellular prion protein (PrP(C)) into an abnormal isoform (PrP(TSE)). Previous studies have shown that N-methyl-D-aspartate (NMDA) receptor antagonists can inhibit glutathione depletion and neurotoxicity induced by PrP(TSE) and a toxic prion protein peptide, PrP106-126, in vitro. NMDA receptor activation is known to increase intracellular accumulation of Ca(2+), resulting in up-regulation of arachidonic acid (AA) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…As illustrated in Figure 1b, a 24-h treatment of cortical cells with 25 mM Ab [25][26][27][28][29][30][31][32][33][34][35] increased the percentage of apoptotic cells, as assessed by 4 0 ,6-diamidino-2-phenylindole (DAPI) staining. This proapoptotic effect of Ab was totally suppressed by a 48-h pretreatment of the cells with the 12-LOX antisense oligonucleotide, whereas the sense or the scramble 12-LOX oligonucleotide did not show any protective action (Figure 1b).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…As illustrated in Figure 1b, a 24-h treatment of cortical cells with 25 mM Ab [25][26][27][28][29][30][31][32][33][34][35] increased the percentage of apoptotic cells, as assessed by 4 0 ,6-diamidino-2-phenylindole (DAPI) staining. This proapoptotic effect of Ab was totally suppressed by a 48-h pretreatment of the cells with the 12-LOX antisense oligonucleotide, whereas the sense or the scramble 12-LOX oligonucleotide did not show any protective action (Figure 1b).…”
Section: Resultsmentioning
confidence: 89%
“…Previous studies indicated that 5-LOX could play a critical role in neuronal cell death, mediating, for instance, kainic acidinduced excitotoxicity 27 and apoptosis generated by prion peptide. 28 We recently reported that the 5-LOX inhibitor, caffeic acid, did not counteract apoptosis induced by Ab in cortical neurons, suggesting that 5-LOX was not involved in this degeneration process. 33 In the present study, we further evaluated this hypothesis through the same strategy as that used for 12-LOX.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations